AD, Volume 6, n° 1, 1981 - Full Issue - RWEYEMAMU, Justinian (Africa Development, 1981)
CONTENTS The Formulation of an Industrial Strategy for Tanzania JUSTINIAN RWEYEMAMU ......................... 5 Les Biens d'Equipement dans l'Industrie Algérienne S. P. THIERRY ........................ 20 The Problem of the State in Backward Capitalist Societies HARRY GALBOURNE ..................... 45 La Problématique de l'Eau en Milieu Rural Ivoirien : Aspects Méthodologiques et Pédagogiques KADJA M. DANIEL .......................... 71 Industrialization and Technological Policy in Tanzania: An Overview H.P.B. MOSHI ................................. 80 FOCUS ON RESEARCH AND TRAINING INSTITUTES Institut de Recherches Scientifique (I.R.S.), Kinshasa I, Zaïre ....................... 97 BOOK REVIEWS Policy Reform in Developing Countries BELA BALASSA ...................... 100 Readings in Social Sciences - Issues in National Development E. C. AMUCHEAZI ..................... 102 BOOK RECEIVED .......................104